2007
DOI: 10.3181/0703-rm-70
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosyl-Cobinamide, a New and Direct Nitric Oxide–Releasing Drug Effective In Vivo

Abstract: A limited number of nitric oxide (NO)-generating drugs are available for clinical use for acute and chronic conditions. Most of these agents are organic nitrates, which do not directly release NO; tolerance to the drugs develops, in part, as a consequence of their conversion to NO. We synthesized nitrosyl-cobinamide (NO-Cbi) from cobinamide, a structural analog of cobalamin (vitamin B12). NO-Cbi is a direct NO-releasing agent that we found was stable in water, but under physiologic conditions, it released NO w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…In a separate experiment, 12 week-old intact female mice (six mice per group) were randomized to receive either vehicle or NO-Cbi on the same dose and schedule for five weeks. This NO-Cbi dose did not significantly reduce systolic blood pressure (< 10 mm Hg), consistent with our previous report, 33 and the NO-Cbi-treated mice showed no signs of toxicity and had similar weight gain during the experiment as the corresponding vehicle-treated groups. Double calcein labeling was performed by intraperitoneal injection of calcein (25 mg/kg) at seven and four days before euthanasia.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…In a separate experiment, 12 week-old intact female mice (six mice per group) were randomized to receive either vehicle or NO-Cbi on the same dose and schedule for five weeks. This NO-Cbi dose did not significantly reduce systolic blood pressure (< 10 mm Hg), consistent with our previous report, 33 and the NO-Cbi-treated mice showed no signs of toxicity and had similar weight gain during the experiment as the corresponding vehicle-treated groups. Double calcein labeling was performed by intraperitoneal injection of calcein (25 mg/kg) at seven and four days before euthanasia.…”
Section: Methodssupporting
confidence: 91%
“…10, 30, 32 Here, we examined the skeletal effects of a novel NO donor, nitrosyl-cobinamide (NO-Cbi), derived from the vitamin B 12 precursor cobinamide; it releases NO directly, without biotransformation or generation of reactive oxygen species. 3336 We found that NO-Cbi enhanced trabecular bone mass in intact and OVX mice by enhancing osteoblast activity and inhibiting osteoclast differentiation.…”
Section: Introductionmentioning
confidence: 82%
“…It is unlikely that physiological concentrations of circulating cobinamides (Ͻ30 pM) or B 12 vitamins (ϳ300 pM) (Hardlei and Nexo, 2009) have any effects on sGC func- Because of high affinity to cyano groups, cobinamides are used for cyanide detoxification (Broderick et al, 2006) and doses of 800 mg/kg are deemed safe for laboratory animals (Brenner et al, 2010). Previous studies reported that nitrosyl-cobinamide functions as an NO donor (Broderick et al, 2007), increasing vasodilation and vasodilator-stimulated phosphoproteinphosphorylation, presumably through NO-dependent activation of sGC. Data presented in the current report suggest that some of these effects may be, in fact, due to the direct NO-independent activation of sGC by the cobinamide macrocycle itself.…”
Section: Discussionmentioning
confidence: 99%
“…In PtK2 cells, a single application of NO-Cbi was sufficient to significantly improve wound healing, while in the other three cell types several low dose drug applications were necessary. Multiple drug administrations were needed, likely because NO-Cbi has a half-life of about 90 min in tissue culture medium [25]. Studies are in progress on different formulations to increase the half-life of NO-Cbi, however, application of NO-Cbi to a wound three or four times a day would not obviate its potential medical use.…”
Section: Discussionmentioning
confidence: 99%
“…A cobinamide solution was thoroughly deoxygenated using argon, the cobalt was reduced from +3 to +2 valence state using a two-molar excess of ascorbic acid, and NO gas (99.99% pure, Matheson Gas Co.) was bubbled through the reduced cobinamide solution [25]. Concentrated stock solutions of NO-Cbi were diluted in deoxygenated sterile water, and the diluted NO-Cbi was added to cells using a Hamilton syringe (Hamilton, Reno, NV).…”
Section: Preparation Of No-cbimentioning
confidence: 99%